Consumer protection in Malaysia an analysis of 10 years legal developments(2000-2010) - Amin, Naemah (2011)
There has been major legislative reform and development in the area of consumer protection in Malaysia for the past 10 years. The Consumer Protection Act 1999 which came into being at the end of 1999 was the milestone for the development. Subsequently, the National Consumer Policy was introduced in 2002 with the aims, inter alia to strengthen the legal protection for consumers through the introduction of new laws and amendments to the existing laws. This paper surveys the major developments of consumer protection law since the introduction of the Consumer Protection Act in 1999.